Palaearctic willow-catkin sawflies: a revision of the amentorum species group of Euura (Hymenoptera, Tenthredinidae) - Liston, Andrew; Vikberg, Veli; Mutanen, Marko; Nyman, Tommi; Prous, Marko (Zootaxa, 2023)
The Euura amentorum species group is Holarctic, and in Europe it is most species-rich in the North. Their larvae develop entirely within the female catkins of Salix species: some species bore in the central stalk, whereas others live outside this and feed mainly on the developing seeds. Eight Palaearctic species are treated here as valid, and a key to these is provided. Males of five species are known. Two new species are described from northern Europe: Euura pohjola sp. n. and E. ursaminor sp. n. First records of E. itelmena (Malaise, 1931) from the West Palaearctic are presented. We propose seven new synonymies: Pontopristia montana Lindqvist, 1961 (junior secondary homonym in Euura) with Euura freyja (Liston, Taeger & Blank, 2009); Pontopristia brevilabris Malaise, 1921, Amauronematus fennicus Lindqvist, 1944, Pontopristia boreoalpina Lindqvist, 1961, Pontopristia punctulata Lindqvist, 1961, and Amauronematus pyrenaeus Lacourt, 1995 with Euura microphyes (Förster, 1854); and Pteronidea holmgreni Lindqvist, 1968 with Nematus umbratus Thomson, 1871. Lectotypes are designated for: Amauronematus fennicus Lindqvist, 1944, Nematus amentorum Förster, 1854, Nematus suavis Ruthe, 1859, Pontopristia brevilabris Malaise, 1921, Pontopristia itelmena Malaise, 1931, Pontopristia kamtchatica Malaise, 1931, Pontopristia lapponica Malaise, 1921, Pontopristia latiserra Malaise, 1921, Pontopristia romani Malaise, 1921, and Pristiphora amentorum var. nigripleuris Enslin, 1916. Many new host plant associations are recorded.